Local Content in English Textbook of Elementary School in Surakarta (Content Analysis) - Ummi Kaltsum, H; ., Susiati (KnE Social Sciences, 2019)
English in elementary school is categorized as a local content curriculum area. Local content should contain local potentials where English is taught therefore the textbook content must have its own distinctive regional characteristics. Through some observations it is found that English textbooks for primary school in Surakarta have not fully accommodated the local content. Most of the textbooks contain general discourse and do not have specific characteristics and potential areas where English is taught. This paper aims to describe how far English textbook for elementary school in Surakarta accommodates its local content using content analysis. The finding shows that the local content is not spread in all skills, and can only be found in 8 skills from total 56 skills, or it is about 14%. English in elementary school is categorized as a local content curriculum area. Local content should contain local potentials for any course taught, including English. Therefore, the textbook content must have its own distinctive regional characteristics. Through some observations conducted, it is found that English textbooks for primary school in Surakarta have not fully accommodated the local content. Most of the textbooks contain general discourse and do not have specific characteristics and potential areas where English is taught. This paper aims to describe how far English textbook for elementary school in Surakarta accommodates its local content by employing a content analysis approach. Keywords: local content, elementary English, content analysis